Epidemiology of traumatic brain injury older inpatients in Chinese military hospitals, 2001–2007. (October 2017) - Li, Yunming; Zhou, Jihong; Chen, Fuqin; Zhang, Junran; Qiu, Jun; Gu, Jianwen
Highlights: TBI among older people in China has increased by a mean yearly rate of 7.78%. The leading causes of TBI are motor vehicle traffic and fall-related incidents. TBI costs average US795 for hospitalization with fatality rate of 9.38%. Study on TBI epidemiology helps to design cost-effective preventive measures. Abstract: The incidence of traumatic brain injury (TBI) among older people has been significantly increased. Understanding the epidemiological characteristics, the causes of injury and the outcomes of TBI among older people provides value evidence for designing preventative measures and therapeutic interventions for TBI. In this study, using ICD-9-CM codes in the Chinese Trauma Database, we identified inpatients aged 65 years and older diagnosed with TBI between 2001 and 2007 in Chinese military hospitals. Demographic characteristics, admission time, injury cause, injury severity, length of stay, hospitalization costs, and outcomes were systematically described. In total, 13, 802 inpatients with TBI (63.13% males and 36.87% females) were identified from over 200 Chinese military hospitals. TBI diagnoses increased by a mean yearly rate of 7.78%; the annual admission peaked during the third quarter of the year, October in particular. The leading causes of TBI were motor vehicle traffic (48.37%) and fall-related incidents (38.89%). The severity of TBI in older inpatients was classified by the Abbreviated Injury Scale as minor (24.31%), serious (19.37%), severe (37.95%), and critical (18.37%). The mean length of stay was 17.87 ± 23.31 days, the median hospitalization cost was US795, and the case fatality rate was 9.38%. These data substantiate that the design and implementation of proven and cost-effective preventive measures focusing on the leading causes of TBI in this population is essential.